Analisis Kelayakan Finansial Pembangunan Saluran Kabel Tegangan Tinggi yang Berdampak Terhadap Penyelesaian Outlet IBT 3,4 Gistet Tambun - Muhammad Ihsan Hardeni; Tri Wahyu Adi (Pusat Riset dan Inovasi Nasional, 2026)
The development of electricity infrastructure is a vital component in supporting economic growth and sustainable energy supply, especially in strategic areas such as Bekasi Regency which is part of the Greater Jakarta metropolitan area. This area is experiencing rapid development as a residential, industrial, and commercial center, thus requiring a reliable and efficient electricity system. This study aims to analyze the financial feasibility of the construction of High Voltage Cable Ducts (SKTT) as an alternative to High Voltage Overhead Ducts (SUTT) for the completion of the IBT 3.4 Tambun outlet, taking into account space limitations in densely populated areas, community resistance, and spatial complexity that often hinder the construction of SUTT in urban areas. Based on the calculation of the present value (PV), the total cost of SKTT is Rp 594,667,106,857 consisting of initial investment and cable replacement in the 25th year which is lower than the total cost of SUTT of Rp 654,218,062,903, which includes construction costs, land acquisition, and maintenance. Sensitivity simulations show that the SKTT remains more economical even if its investment costs increase by up to 10%. These results demonstrate that the SKTT is a technically, socially, and financially feasible solution for densely populated areas like Bekasi.